A prospective cohort study of the association between mode of delivery and postpartum posttraumatic stress disorder - Baohong Xu; Yanfang Chen; Jiao Tang (Scientific Reports)
Abstract Previous studies investigating the correlation between mode of delivery and posttraumatic stress disorder (PTSD) have yielded inconsistent results. This study aims to investigate the association between mode of delivery and PTSD in a cohort of Chinese women with a high rate of cesarean section (CS). We conducted a prospective cohort study in China between October 2019 and June 2021. Women aged 20–45 years who give birth at The Seventh Hospital of the Southern Medical University during the study period were enrolled. PTSD was assessed by the Posttraumatic Stress Disorder Checklist-Civilian Version at 42 days postpartum. We examined the independent association between mode of birth and PTSD by log-binomial regression analysis. A total of 759/800 (94.88%) women completed questionnaire. The prevalence of postpartum PTSD was 12.12% in included women, 8.18% in women with vaginal delivery (VD), 17.55% in women with CS. After adjusting for confounding factors, it was found that women with elective CS (RR = 1.70, 95%CI, 1.03 to 2.87) and emergency CS (RR = 1.95, 95%CI, 1.08 to 3.83) had an increased risk of developing postpartum PTSD compared with women with VD. CS is identified as an independent risk factor for PTSD in a cohort of Chinese women with a high prevalence of CS.